A six-factor extension of the Fama-French asset pricing model – the case of the Polish stock market - Nagy, Bálint Zsolt; Dezméri, Tünde (Publishing House of Wroclaw University of Economics and Business, 2022)
Multifactor asset pricing models evolved at an accelerated pace in the past few years after the publication of the Fama and French five-factor model. Despite the results from developed markets which arguably make the sixth momentum factor redundant, the authors showed in this study that in an emerging market, e.g. the Warsaw Stock Exchange, the momentum factor (persistence of returns) is still a major asset pricing factor. The data covers the period 2010-2018 on a monthly granularity, during which the Polish stock market was still considered ‘emerging’.
Argumenta Oeconomica, 2022, Nr 2 (49), s. 5-22
Keywords: multifactor asset pricing; momentum; Warsaw Stock Exchange